Strategies to Overcome Autofluorescence in Nanoprobe‐Driven In Vivo Fluorescence Imaging. Issue 9 (19th June 2018) - del Rosal, Blanca; Benayas, Antonio
Abstract: The development of fluorescent probes and optical detection systems in the near‐infrared (700–2000 nm) has boosted the interest in fluorescence bioimaging as an alternative to traditional medical imaging techniques. Fluorescence imaging can provide high‐resolution images at fast acquisition speeds, while removing the need for ionizing radiations or radioactive contrast agents and requiring relatively simple and cost‐effective equipment. The low absorption and scattering of near‐infrared radiation by biological tissues enables minimally invasive visualization of deeply embedded organs and structures. However, the infrared autofluorescence background generated by some biological components, as discussed here, can negatively affect the image contrast and complicate the visualization of the fluorescent probes used as contrast agents. A critical review on the different approaches for improving the signal‐to‐noise ratio in in vivo fluorescence imaging experiments through autofluorescence background removal is presented here. Abstract : Tissue autofluorescence is the major contributor to background noise in in vivo NIR images, so that it complicates the detection of any NIR fluorescent marker used as a contrast agent. A critical review of the numerous experimental approaches devised to perform in vivo autofluorescence‐free images, together with a discussion on the main autofluorescence sources in the NIR, is presented.